PD-L1 and PD-L2 gene expression in human glioblastoma cells resistant to chemo- and radiotherapy - A. A. Pinevich; N. L. Vartanyan; L. N. Kiseleva; I. I. Bode; I. Yu. Krutetskaya; A. V. Kartashev; V. E. Makarov; T. E. Poneza; I. V. Smirnov; M. P. Samoilovich (Медицинская иммунология)
Membrane molecules PD-L1 and PD-L2, ligands of T lymphocytes PD1 receptor, perform immunoregulatory functions. Their binding to the receptor leads to inhibition of proliferation, reduction of cytokine production, cytotoxic response, and apoptosis of T lymphocytes. The cells of many tumors, regardless of their histogenesis, express PD-L1 molecules, thus limiting the development of an anti-tumor immune response. Glioblastomas are highly malignant recurrent tumors of the central nervous system. The main sources of glioblastoma recurrence are resistant tumor cells initially present in gliomas with heterogeneous cellular composition, as well as resistant cells that are formed during therapy. Increasing the dose of cytostatic drugs or radiation during relapse therapy is not effective in glioblastomas. It has been shown for a number of tumors, including ovarian cancer and non-small cell lung cancer, that drugs preventing PD-L1/PD1 interaction are effective in the treatment of neoplasms resistant to chemo- and radiotherapy. Immunotherapy using drugs that inhibit the binding of PD-L molecules to their receptor is considered as a way to overcome the resistance of glioblastomas to therapy. The aim of this work was to assess the level of PD-L1 and PD-L2 gene expression in resistant glioblastoma cells lines A172, R1, T2 and T98G, which resumed proliferation after exposure to the maximum for each line, sublethal doses of cytostatic drugs (fotemustine and temozolomide), fractionated or single gamma irradiation. A172 line belongs to glioblastomas that are highly sensitive to these influences, T98G is a highly resistant cell line, while R1 and T2 lines occupy an intermediate position. In intact glioblastoma A172, R1, and T2 cells the level of PD-L1 and PD-L2 gene expression was equally high, while in T98G cells it was significantly lower. Exposure of A172 and R1 glioblastoma lines to cytostatic drugs or irradiation did not significantly change the level of PD-L1 and PD-L2 genes expression typical for intact cells. In T2 glioblastoma cells, and especially in T98G cells, a significant increase in expression of these genes was found, most pronounced for PD-L2 gene. This increase in expression may indicate an enhanced malignancy of resistant T2 and T98G cells. High expression of the genes responsible for the production of PD-L1 and PD-L2, which limit the cytotoxic response against tumor cells, is a prerequisite for the use of drugs targeted against PD-L1 and PD-L2 for the elimination of resistant cells in glioblastoma.